Pengaruh Kecerdasan Emosional, Kecerdasan Spiritual, dan Perilaku Belajar pada Tingkat Pemahaman Akuntansi - Agustin, Ida Ayu Clara; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 25 No 2 (2018)DO - 10.24843/EJA.2018.v25.i02.p07, 2018)
Accounting understanding is a process of an accounting student in understanding matters related to accounting. Students' accounting understanding is not only shown from the values ??obtained in the course but also influenced by several factors. The purpose of this study was to determine the effect of emotional intelligence, spiritual intelligence, and learning behavior on the level of understanding of accounting for non-regular students of the 2014 accounting department at the Faculty of Economics and Business at Udayana University. The method of determining the sample of this study uses purposive sampling method using the Slovin formula. Data collection using questionnaires distributed directly to students as many as 126 questionnaires. The data analysis technique used is multiple linear regression. Based on the results shows that emotional intelligence, spiritual intelligence, and learning behavior have a positive effect on the level of understanding of accounting. Keywords: understanding, emotional, spiritual, learning behavior